Polyurethane carbon nanotube composite filler for water treatment, preparation method and use thereof
By adhering carbon nanotubes and active particles to the polyurethane sponge, polyurethane carbon nanotube composite filler is formed, which solves the problems of poor mechanical properties and insufficient hydrophilicity of the polyurethane filler, and achieves more efficient wastewater treatment and longer service life.
Patent Information
- Application Number
- CN202110812156.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing polyurethane fillers have poor mechanical properties and are easily dissipated in wastewater treatment, and have insufficient hydrophilicity and biofilm formation capabilities, resulting in poor sewage treatment effect and short service life.
Through physical and chemical blending loading technology, dopamine modified solution is used to adhere carbon nanotubes and active particles to the polyurethane sponge framework to form polyurethane carbon nanotube composite filler, enhancing the mechanical properties and biofilm formation ability of the filler.
It improves the specific surface area, hydrophilicity and microbial adhesion of the filler, significantly improves the sewage treatment effect, extends the service life of the filler, and reduces replacement costs and operating costs.
Smart Images

Figure BDA0003168777270000141 
Figure BDA0003168777270000142 
Figure BDA0003168777270000151
Abstract
Description
Technical Field
[0001] The invention belongs to the field of sewage biological treatment materials and relates to a polyurethane carbon nanotube composite filler for water treatment, a preparation method and application thereof. Background Art
[0002] Based on the properties of the materials, traditional fillers in biological wastewater treatment can be divided into three categories: inorganic fillers, active organic fillers and inert organic fillers. Inorganic fillers mainly include zeolite, volcanic rock, ceramics, activated carbon, etc., which have excellent mechanical strength, rough surface, large internal pores, but the formation of biofilm is relatively slow, permeability is poor, and easy to clog. Active organic fillers mainly refer to agricultural waste such as bamboo fiber, corn cobs, cotton stalks, etc., which have good hydrophilicity and biocompatibility, but low mechanical strength and poor mass transfer performance. Traditional inert organic fillers such as polyethylene, polyester, polyurethane (PU), etc. have good stability, but due to poor hydrophilicity, they have poor biological affinity, which is not conducive to the formation of biofilm.
[0003] At present, the research on biofilm fillers at home and abroad mainly focuses on improving the performance of fillers through chemical grafting, physical and chemical blending and other methods on the basis of existing traditional fillers to improve their effect in sewage treatment. Taking polyurethane fillers as an example, CN201910787664.X discloses a modification method using a modifier to make the surface of polyurethane fillers have hydrophilic groups such as hydroxyl and carboxyl groups; CN202010172275.9 loads self-generating materials on the surface of polyurethane to provide electron donors for dehalogenating respiratory bacteria and is used for groundwater remediation; CN201910076818.4 combines biofilm technology, adds tourmaline powder in the process of polyurethane preparation to prepare tourmaline / polyurethane composite fillers, thereby increasing the biofilm growth rate and increasing biomass; C N201811038738.1 uses a mixed solution of neutral red, nitrite and acid to modify the hydrophilicity of polyurethane; CN201110428036.6 uses an aqueous solution of acrylic acid and sulfuric acid with tetravalent cerium ions as an initiator to perform surface graft copolymerization modification on the foamed and ozone surface pretreated polyurethane to improve its hydrophilicity; CN201911213123.2 obtains a polyurethane biofiller with more functional groups by cleaning and roughening the polyurethane sponge and immersing it in an aqueous solution of potassium methyl silicate and an aqueous solution of asparagine.
[0004] It can be seen from the above technologies that currently the main focus is on chemical functional group modification or surface loading modification of polyurethane to increase hydrophilicity and specific surface area, but there is little involvement in the modification of the poor mechanical friction and wear properties of polyurethane materials after long-term use in actual applications.
[0005] Therefore, the art needs a polyurethane biofiller with large specific surface area, good hydrophilicity, good microbial adhesion, good sewage treatment effect, good mechanical properties, low wear and tear, and long service life. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention proposes a novel polyurethane filler modified by carbon nanotubes (CNT), a preparation method and application thereof. The present invention solves the problems of poor mechanical properties and easy loss of traditional polyurethane fillers, increases the biomass loaded on the surface of the filler through physical and chemical blending loading, enhances the sewage treatment effect of the filler, prolongs the service life of the filler, reduces replacement costs, and reduces operating costs.
[0007] Specifically, the present invention provides a polyurethane carbon nanotube composite filler for water treatment, wherein the polyurethane carbon nanotube composite filler comprises a polyurethane sponge, carbon nanotubes adhered to a polyurethane sponge skeleton via polydopamine, and active particles with an adsorption function.
[0008] In one or more embodiments, the specific surface area of the polyurethane carbon nanotube composite filler is 3.4-3.8 m 2 / g.
[0009] In one or more embodiments, the carbon nanotubes are hydroxylated carbon nanotubes, carboxylated carbon nanotubes, or carbonylated carbon nanotubes.
[0010] In one or more embodiments, the carbon nanotubes are multi-walled carbon nanotubes.
[0011] In one or more embodiments, the carbon nanotubes have a diameter of 20-30 nm and a length of 10-30 μm.
[0012] In one or more embodiments, the particle size of the polyurethane sponge is 10-50 mm.
[0013] In one or more embodiments, the polyurethane sponge is insoluble in water.
[0014] In one or more embodiments, the active particles are selected from one or more of activated carbon, iron disulfide powder, and zeolite.
[0015] In one or more embodiments, the active particles have a particle size of 100-200 mesh.
[0016] The present invention also provides a method for preparing the polyurethane carbon nanotube composite filler described in any one of the items herein, the method comprising:
[0017] (1) preparing a dopamine modified solution: adding dopamine to a tris-HCl buffer solution and mixing the mixture uniformly to obtain a dopamine modified solution;
[0018] (2) Preparing a carbon nanotube modified solution, an active particle modified solution and / or a composite modified solution:
[0019] dispersing carbon nanotubes in a dopamine modified solution to obtain a carbon nanotube modified solution,
[0020] dispersing the active particles in the dopamine modified solution to obtain an active particle modified solution, and / or
[0021] dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution;
[0022] (3) contacting the polyurethane sponge with a carbon nanotube modification solution, an active particle modification solution and / or a composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
[0023] In one or more embodiments, the pH of the tris-HCl buffer solution is 8-9.
[0024] In one or more embodiments, the concentration of tris(hydroxymethyl)aminomethane in the tris-HCl buffer solution is 0.05-0.1 mol / L.
[0025] In one or more embodiments, the concentration of dopamine in the dopamine-modified solution is 2-3 g / L.
[0026] In one or more embodiments, in the carbon nanotube modified solution, the mass ratio of carbon nanotubes to dopamine is 1:4-6.
[0027] In one or more embodiments, in the active particle modified solution, the mass ratio of active particles to dopamine is 2:3 to 3:2.
[0028] In one or more embodiments, in the composite modified solution, the mass ratio of carbon nanotubes to dopamine is 1:4-6.
[0029] In one or more embodiments, in the composite modified solution, the mass ratio of carbon nanotubes to active particles is 1:4-6.
[0030] In one or more embodiments, when preparing the carbon nanotube modified solution, the active particle modified solution and the composite modified solution, the solution system is ultrasonically dispersed, and the ultrasonic dispersion time is preferably 20-40 minutes.
[0031] In one or more embodiments, when the polyurethane sponge is contacted with the carbon nanotube modification solution, the active particle modification solution and the composite modification solution, the volume ratio of the polyurethane sponge to the carbon nanotube modification solution, the active particle modification solution or the composite modification solution is 5:95 to 20:80.
[0032] In one or more embodiments, the polyurethane sponge is contacted with the carbon nanotube modification solution, the active particle modification solution or the composite modification solution for 16-28 hours.
[0033] In one or more embodiments, when the polyurethane sponge is in contact with the carbon nanotube modified solution, the active particle modified solution and the composite modified solution, the reaction system of the polyurethane sponge and the carbon nanotube modified solution, the active particle modified solution or the composite modified solution is stirred, and the stirring rate is preferably 200-350rpm, and the stirring time is preferably 16-28h.
[0034] In one or more embodiments, the method further comprises washing and drying the polyurethane sponge after contacting the polyurethane sponge with the carbon nanotube modification solution, the active particle modification solution and / or the composite modification solution.
[0035] In one or more embodiments, the drying temperature is 75-90° C. and the drying time is 12-16 hours.
[0036] The present invention also provides use of the polyurethane carbon nanotube composite filler described in any embodiment of the present invention in a biofilm reactor or water treatment.
[0037] In one or more embodiments, the biofilm reactor is a moving bed biofilm reactor.
[0038] The present invention also provides a biofilm reactor, wherein the biofilm reactor is filled with the polyurethane carbon nanotube composite filler described in any embodiment of the present invention; preferably, the biofilm reactor is a moving bed biofilm reactor.
[0039] The present invention also provides a water treatment device comprising the biofilm reactor according to any embodiment of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the preparation process of PU / CNT composite filler in Example 1.
[0041] Figure 2 Schematic diagram of the water treatment experimental device in Test Example 3. Figure 2 In the figure, 1 is a water inlet tank, 2 is a biofilm reactor inlet, 3 is a biofilm reactor, 4 is a biofilm reactor outlet, 5 is a stirrer, 6 is a dissolved oxygen (DO) tester, 7 is a water bath inlet, 8 is a water bath outlet, 9 is a rotor flowmeter, and 10 is an aeration pump. DETAILED DESCRIPTION
[0042] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0043] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0044] Herein, the terms "comprising", "including", "containing", "having" and similar terms cover the meanings of "essentially consisting of" and "consisting of", for example, when "A comprises B and C" is disclosed herein, it should be considered that "A consists of B and C" has been disclosed herein.
[0045] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0046] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.
[0047] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0048] Based on the polyurethane sponge, the present invention utilizes the self-polymerization property of dopamine in a buffer solution to make carbon nanotubes and active particles with adsorption function adhere to the skeleton of the polyurethane sponge, thereby obtaining a polyurethane filler that can be used for sewage biological treatment and has large specific surface area, good hydrophilicity, good microbial adhesion, good sewage treatment effect, good mechanical properties, low wear and tear, and long service life.
[0049] Polyurethane sponge is a material with a porous structure and a polyurethane skeleton. The polyurethane sponge suitable for the present invention is a hydrophilic polyurethane sponge, which means that microorganisms in water can adhere to the surface of the polyurethane sponge. The polyurethane sponge suitable for the present invention is insoluble in water and can basically maintain its original shape in water. The specific surface area of the polyurethane sponge can be 3.0-3.4m 2 / g, for example 3.1-3.2m 2 / g. The shape of the polyurethane sponge is not particularly limited, and may be, for example, block, spherical, cylindrical, etc. The particle size (equivalent diameter) of the polyurethane sponge may be 10-50 mm, for example, 25-45 mm. For example, the polyurethane sponge may be a block polyurethane sponge of 20±5 mm×20±5 mm×20±5 mm.
[0050] The carbon nanotubes suitable for the present invention are hydrophilic carbon nanotubes, including but not limited to hydroxylated carbon nanotubes, carboxylated carbon nanotubes, carbonylated carbon nanotubes, etc., which are characterized by having hydrophilic groups on the surface of the carbon nanotubes, such as hydroxyl groups, carboxyl groups, carbonyl groups, etc. The carbon nanotubes can be multi-walled carbon nanotubes or single-walled carbon nanotubes. In some embodiments, the carbon nanotubes are multi-walled carbon nanotubes. The diameter of the carbon nanotubes suitable for the present invention is preferably 20-30 nm, and the length is preferably 10-30 μm.
[0051] In the present invention, active particles refer to powdered materials with adsorption function. The active particles are preferably selected from one or more of activated carbon (AC), iron disulfide (FeS2) powder and zeolite. In some embodiments, the active particles are activated carbon. In some embodiments, the active particles are FeS2. The particle size of the active particles is preferably 100-200 mesh.
[0052] In the polyurethane carbon nanotube composite filler of the present invention, carbon nanotubes and active particles are adhered to the skeleton of the polyurethane sponge through polydopamine. Under the combined action of dissolved oxygen and pH in the solution, the catechol structure in dopamine is oxidized into a benzoquinone structure. When the amino group is protonated, a 1,4-Michael cyclization reaction occurs between molecules to generate a dopamine complex, and the dopamine complex itself is easily oxidized, and further generates 5,6-dihydroxyindole through intramolecular rearrangement. 5,6-dihydroxyindole is unstable and easily oxidized to generate indolequinone, and finally generates polydopamine through intermolecular cross-linking reaction. Polydopamine can form a covalent bond with the surface of the substrate through Michael addition reaction or Schiff base reaction, so as to firmly adhere to the surface of the substrate.
[0053] The polyurethane carbon nanotube composite filler of the present invention can be prepared by a method comprising the following steps:
[0054] (1) preparing a dopamine modified solution: adding dopamine to a tris-HCl buffer solution and mixing the mixture uniformly to obtain a dopamine modified solution;
[0055] (2) Preparing a carbon nanotube modified solution, an active particle modified solution and / or a composite modified solution:
[0056] dispersing carbon nanotubes in a dopamine modified solution to obtain a carbon nanotube modified solution,
[0057] dispersing the active particles in the dopamine modified solution to obtain an active particle modified solution, and / or
[0058] dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution;
[0059] (3) contacting the polyurethane sponge with a carbon nanotube modification solution, an active particle modification solution and / or a composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
[0060] The tris-HCl buffer solution is a buffer system formed by dissolving tris (tris) and HCl in water. The pH of the tris-HCl buffer solution suitable for the present invention can be 8-9, for example 8.5. In the tris-HCl buffer solution, the concentration of tris can be 0.05-0.1 mol / L. The tris-HCl buffer solution of the desired concentration and pH can be prepared by mixing a certain concentration of tris aqueous solution and an HCl aqueous solution, and optionally adjusting the pH and diluting.
[0061] In the present invention, the concentration of dopamine in the dopamine-modified solution is preferably 2-3 g / L, which is conducive to adhering the carbon nanotubes and active particles to the polyurethane sponge skeleton.
[0062] It is understood that in the present invention, in order to make both carbon nanotubes and active particles adhere to the polyurethane sponge skeleton, one or more of carbon nanotube modified solution, active particle modified solution and composite modified solution can be selected, provided that only carbon nanotube modified solution or only active particle modified solution can not be configured, for example, only composite modified solution can be configured, or two or three of carbon nanotube modified solution, active particle modified solution and composite modified solution can be configured. Accordingly, polyurethane sponge can be contacted with composite modified solution only, or polyurethane sponge can be contacted with two or three of carbon nanotube modified solution, active particle modified solution and composite modified solution successively. If necessary, multiple different carbon nanotube modified solution, active particle modified solution and / or composite modified solution can be configured, and polyurethane sponge can be contacted with multiple different carbon nanotube modified solution, active particle modified solution and / or composite modified solution.
[0063] In the present invention, in the carbon nanotube modified solution, the mass ratio of carbon nanotubes to dopamine is preferably 1:4-6. In the active particle modified solution, the mass ratio of active particles to dopamine is preferably 2:3 to 3:2. In the composite modified solution, the mass ratio of carbon nanotubes to dopamine is preferably 1:4-6, and the mass ratio of carbon nanotubes to active particles is preferably 1:4-6. Controlling the mass ratio between carbon nanotubes, dopamine and active particles within the above range is conducive to adhering carbon nanotubes and active particles to the polyurethane sponge skeleton, improving the specific surface area, hydrophilicity, microbial adhesion, sewage treatment effect and mechanical properties of the filler.
[0064] When preparing the carbon nanotube modified solution, the active particle modified solution and the composite modified solution, it is preferred to perform ultrasonic dispersion on the solution system, and the ultrasonic dispersion time may be 20-40 min, for example, 30±5 min.
[0065] It is understandable that the "polyurethane sponge" mentioned in this article when describing the preparation method of the polyurethane carbon nanotube composite filler does not only refer to the polyurethane sponge raw material, but its meaning covers the polyurethane sponge raw material and the polyurethane sponge with carbon nanotubes and / or active particles adhered to it. Those skilled in the art can confirm its specific meaning based on the actual preparation steps.
[0066] In the present invention, before using the polyurethane sponge, the polyurethane sponge may be ultrasonically cleaned to remove dirt on its surface. Ethanol may be used for ultrasonic cleaning. The ultrasonic cleaning time may be 1-30 min, for example, 10±5 min. Drying is usually performed after cleaning.
[0067] It is understood that, in the present invention, the time for which the polyurethane sponge is in contact with the carbon nanotube modified solution, the active particle modified solution or the composite modified solution should be sufficient to allow the carbon nanotubes and / or active particles in the solution to adhere to the polyurethane sponge skeleton, for example, the contact time may be 16-28 hours, for example, 24±2 hours. The temperature during contact may be room temperature (for example, 15-20° C.). The contact may be carried out by placing the polyurethane sponge in the solution. The polyurethane sponge may be stirred when in contact with these solutions, and the stirring rate may be 200-350 rpm, for example, 250±20 rpm, and the stirring may be magnetic stirring.
[0068] When the polyurethane sponge is contacted with at least two of the carbon nanotube modified solution, the active particle modified solution and the composite modified solution in sequence, the order in which the polyurethane sponge contacts the carbon nanotube modified solution, the active particle modified solution and the composite modified solution is not particularly limited. For example, the polyurethane sponge may be contacted with the carbon nanotube modified solution first and then with the active particle modified solution, or the polyurethane sponge may be contacted with the active particle modified solution first and then with the carbon nanotube modified solution.
[0069] In some embodiments, the method of the present invention includes preparing a carbon nanotube modification solution and an active particle modification solution, first contacting the polyurethane sponge with the carbon nanotube modification solution so that the carbon nanotubes adhere to the polyurethane sponge skeleton, and then contacting with the active particle modification solution so that the active particles adhere to the polyurethane sponge skeleton. In other embodiments, the method of the present invention includes preparing a composite modification solution, contacting the polyurethane sponge with the composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton together.
[0070] In the present invention, when the polyurethane sponge is in contact with the carbon nanotube modified solution, the active particle modified solution or the composite modified solution, the volume ratio of the polyurethane sponge to the solution is preferably 5:95 to 20:80, for example, 10:90. Herein, "filling rate" refers to the ratio of the volume of the filler to the total volume of the filler and the filled material, for example, "placing the polyurethane sponge in the liquid with a filling rate of 10%" means that the volume ratio of the polyurethane sponge to the liquid is 10:90. In the present invention, the volume of the polyurethane sponge and the filler refers to the apparent volume, including the solid volume (skeleton matrix) and the pore volume.
[0071] In the present invention, after the polyurethane sponge is contacted with the carbon nanotube modified solution, the active particle modified solution and / or the composite modified solution, the polyurethane sponge can be washed and dried. It can be washed with water (e.g., deionized water). The drying temperature can be 75-90°C, and the drying time can be 12-16h. Drying can be vacuum drying. In some embodiments, each time the polyurethane sponge is contacted with the carbon nanotube modified solution, the active particle modified solution or the composite modified solution, it is washed and dried, and then the dried polyurethane sponge is contacted with the subsequent carbon nanotube modified solution, the active particle modified solution or the composite modified solution. When the polyurethane sponge adheres to the carbon nanotubes and active particles by contacting with the carbon nanotube modified solution, the active particle modified solution and / or the composite modified solution, after the final washing and drying, the polyurethane carbon nanotube composite filler of the present invention is obtained.
[0072] The present invention includes a polyurethane carbon nanotube composite filler prepared by the method described in any embodiment of the present invention.
[0073] The polyurethane carbon nanotube composite filler of the present invention can be used as a biofilm filler for water treatment, for example, filled into a biofilm reactor. In this article, water treatment includes sewage treatment. Sewage can be rural sewage, urban sewage, etc. The sewage treated by the polyurethane carbon nanotube composite filler of the present invention can be sewage with excessive chemical oxygen demand, ammonia nitrogen content and / or total phosphorus content, for example, chemical oxygen demand exceeds 100 mg / L, ammonia nitrogen content exceeds 20 mg / L, and total phosphorus content exceeds 5 mg / L. In some embodiments, the sewage treated by the polyurethane carbon nanotube composite filler of the present invention has one or more of the following water quality characteristics:
[0074] The chemical oxygen demand does not exceed 500 mg / L, for example, 100-300 mg / L;
[0075] Ammonia nitrogen content does not exceed 100 mg / L, for example 20-50 mg / L;
[0076] The total phosphorus content does not exceed 20 mg / L, for example 5-15 mg / L.
[0077] Herein, biofilm refers to the film formed by bacteria and other microorganisms attached to the surface of the filler and their secretions during use. Biofilm filler refers to filler that forms a biofilm on the surface during use. Biofilm reactor refers to a reaction device that uses biofilm filler to purify sewage. In the present invention, the biofilm reactor can be a moving bed biofilm reactor (MBBR), which is characterized in that the biofilm grows on smaller carrier units, and the carriers move freely with the water flow in the reactor.
[0078] The biofilm reactor and water treatment device of the present invention can be constructed as conventional in the art. An exemplary water treatment device including a biofilm reactor is as follows: Figure 2 As shown. The biofilm reactor 3 is a reactor filled with biofilm filler for sewage purification, and has a water inlet and a water outlet, which respectively supply water 2 to the biofilm reactor and water 4 to the biofilm reactor. A temperature control device (such as a water bath), an agitator 5, an aeration tube, a sieve plate and / or a water quality tester (such as a dissolved oxygen tester 6) can be provided on the biofilm reactor 3. The water bath has a water inlet and a water outlet, which respectively supply water 7 to the water bath and water 8 to the water bath. In addition to the biofilm reactor 3, the water treatment device of the present invention may also include components such as a water inlet tank 1, a flow meter (such as a rotor flow meter 9) and an aeration pump 10.
[0079] When the polyurethane carbon nanotube composite filler of the present invention is filled in a biofilm reactor, its filling rate (ratio of the filler volume to the total volume of the filler and water) can be 10-50%, for example, 30±10%.
[0080] The present invention has the following advantages: the surface area of the polyurethane carbon nanotube composite filler of the present invention is large, the carbon nanotubes adhered to the polyurethane sponge skeleton are conducive to improving the mechanical properties and wear resistance of the filler, and increasing the service life of the filler, the hydrophilic carbon nanotubes make the polyurethane surface grafted with more hydrophilic groups, improve the hydrophilicity and biocompatibility, and are conducive to the attachment of microorganisms, the addition of active particles further increases the specific surface area of the filler, and under the synergistic effect of the carbon nanotubes and the active particles, the sewage treatment effect of the filler is significantly improved compared with the ordinary polyurethane sponge filler. The polyurethane carbon nanotube composite filler of the present invention is suitable for an integrated moving bed biofilm reactor, and is particularly suitable for the treatment of rural sewage, simplifying the treatment process.
[0081] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The materials in the examples can all be purchased through commercial sources.
[0082] The following materials were used in the examples:
[0083] Polyurethane sponge: Block polyurethane sponge filler (20 mm × 20 mm × 20 mm) was purchased from Jiangsu Aiqin Environmental Protection Co., Ltd.;
[0084] Tris-HCl buffer solution: Mix 500 mL of 0.1 mol / L tris(hydroxymethyl)aminomethane solution with 73.5 mL of 0.1 mol / L hydrochloric acid solution, adjust the pH to 8.5, and make up to 1 L;
[0085] Carbon nanotube powder: multi-walled hydroxylated carbon nanotube powder, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., with a length of 10-30 μm and a diameter of 20-30 nm;
[0086] Activated carbon powder: particle size is 100 mesh, purchased from Henan Tannuo Activated Carbon Company;
[0087] Iron disulfide powder: particle size is 100 mesh, purchased from Henan Junliao Metallurgical Materials Co., Ltd.
[0088] Example 1
[0089] like Figure 1 As shown, this embodiment prepares a PU / CNT composite filler by the following steps:
[0090] (1) The polyurethane sponge was ultrasonically cleaned with anhydrous ethanol for 10 min and dried;
[0091] (2) adding dopamine to the tris-HCl buffer solution to prepare a solution with a dopamine concentration of 2 g / L;
[0092] (3) taking the solution obtained in step (2), adding carbon nanotube powder, the amount of carbon nanotube powder added is 0.5 g / L, and ultrasonically dispersing for 30 min;
[0093] (4) placing the polyurethane sponge dried in step (1) into the solution prepared in step (3) at a filling rate of 10%;
[0094] (5) subjecting the mixed solution obtained in step (4) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0095] (6) The filler was taken out, washed repeatedly with deionized water, and vacuum dried at a temperature of 80° C. for 12 h to obtain a PU / CNT composite filler.
[0096] Example 2
[0097] In this embodiment, a PU / CNT / activated carbon composite filler is prepared by the following steps:
[0098] (1) The polyurethane sponge was ultrasonically cleaned with anhydrous ethanol for 10 min and dried;
[0099] (2) adding dopamine to the tris-HCl buffer solution to prepare a solution with a dopamine concentration of 2 g / L;
[0100] (3) taking the solution obtained in step (2), adding carbon nanotube powder, the amount of carbon nanotube powder added is 0.5 g / L, and ultrasonically dispersing for 30 min;
[0101] (4) placing the polyurethane sponge dried in step (1) into the solution prepared in step (3) at a filling rate of 10%;
[0102] (5) subjecting the mixed solution obtained in step (4) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0103] (6) taking out the filler, washing it repeatedly with deionized water, and vacuum drying it at a temperature of 80° C. for 12 h to obtain a PU / CNT composite filler;
[0104] (7) Add activated carbon powder to the solution obtained in step (2) at an amount of 3 g / L and perform ultrasonic dispersion for 30 min;
[0105] (8) placing the PU / CNT composite filler obtained in step (6) into the solution prepared in step (7) at a filling rate of 10%;
[0106] (9) subjecting the mixed solution obtained in step (8) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0107] (10) The filler was taken out, washed repeatedly with deionized water, and then vacuum dried at a temperature of 80° C. for 12 h to obtain a PU / CNT / activated carbon composite filler.
[0108] Example 3
[0109] In this embodiment, a PU / CNT / activated carbon composite filler is prepared by the following steps:
[0110] (1) The polyurethane sponge was ultrasonically cleaned with anhydrous ethanol for 10 min and dried;
[0111] (2) adding dopamine to the tris-HCl buffer solution to prepare a solution with a dopamine concentration of 2 g / L;
[0112] (3) Take the solution obtained in step (2), add carbon nanotube powder and activated carbon powder, the amount of carbon nanotube powder added is 0.5 g / L, the amount of activated carbon powder added is 3 g / L, and ultrasonic dispersion is performed for 30 minutes;
[0113] (4) placing the polyurethane sponge dried in step (1) into the solution prepared in step (3) at a filling rate of 10%;
[0114] (5) subjecting the mixed solution obtained in step (4) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0115] (6) The filler was taken out, washed repeatedly with deionized water, and vacuum dried at a temperature of 80° C. for 12 h to obtain a PU / CNT / activated carbon composite filler.
[0116] Example 4
[0117] In this embodiment, a PU / CNT / iron disulfide composite filler is prepared by the following steps:
[0118] (1) The polyurethane sponge was ultrasonically cleaned with anhydrous ethanol for 10 min and dried;
[0119] (2) adding dopamine to the tris-HCl buffer solution to prepare a solution with a dopamine concentration of 2 g / L;
[0120] (3) taking the solution obtained in step (2), adding carbon nanotube powder, the amount of carbon nanotube powder added is 0.5 g / L, and ultrasonically dispersing for 30 min;
[0121] (4) placing the polyurethane sponge dried in step (1) into the solution prepared in step (3) at a filling rate of 10%;
[0122] (5) subjecting the mixed solution obtained in step (4) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0123] (6) taking out the filler, washing it repeatedly with deionized water, and vacuum drying it at a temperature of 80° C. for 12 h to obtain a PU / CNT composite filler;
[0124] (7) Take the solution obtained in step (2), add iron disulfide powder and activated carbon powder in an amount of 3 g / L, and ultrasonically disperse for 30 min;
[0125] (8) placing the PU / CNT composite filler obtained in step (6) into the solution prepared in step (7) at a filling rate of 10%;
[0126] (9) subjecting the mixed solution obtained in step (8) to magnetic stirring at a speed of 250 rpm for 24 h at room temperature (15-20° C.);
[0127] (10) The filler was taken out, washed repeatedly with deionized water, and then vacuum dried at a temperature of 80° C. for 12 h to obtain a PU / CNT / iron disulfide composite filler.
[0128] Test Example 1
[0129] The raw material polyurethane sponge and the composite filler prepared in Example 1 were tested for mechanical properties and wear properties, and the results are shown in Table 1. The mechanical properties (elastic modulus and tensile strength) were measured using a universal electronic testing machine in accordance with GB 13022-1991 standard, with a sample width of 20 mm, a sample gauge length of 10 mm, and a tensile rate of 500 ± 5 mm / min. The wear properties (wear amount and wear rate) were measured using a UMT-3 wear tester, with a rotation speed n of 500 rpm, a loading force P of 250 N, a friction radius of 25 mm, a test time of 30 min, and the experiment was conducted at room temperature. The friction ball was a GCr15 steel ball, and the friction torque was recorded by a friction torque sensor. The sample was weighed before and after the experiment, and the wear amount and wear rate were calculated.
[0130] Table 1: Mechanical properties and wear properties of polyurethane sponge and composite filler prepared in Example 1
[0131]
[0132] The results in Table 1 show that adhering carbon nanotubes to polyurethane sponge significantly improves the tensile strength and wear resistance of the polyurethane sponge, thereby greatly extending its service life as a filler, reducing replacement costs, and lowering operating expenses.
[0133] Test Example 2
[0134] The specific surface area of the raw polyurethane sponge and the composite fillers prepared in Examples 1-4 were tested by BET physical adsorption method. The results are shown in Table 2.
[0135] Table 2: Specific surface area of polyurethane sponge and composite fillers prepared in Examples 1-4
[0136]
[0137] The results in Table 2 show that adhering carbon nanotubes to the polyurethane sponge increases the specific surface area of the polyurethane sponge, and further adhering active particles to the polyurethane sponge further increases the specific surface area of the polyurethane sponge, thereby improving the bioloading capacity of the filler.
[0138] Test Example 3
[0139] The raw material polyurethane sponge and the composite fillers prepared in Example 2 and Example 4 were filled into the Figure 2 The wastewater treatment experiment was carried out in the biofilm reactor of the water treatment experimental device shown in FIG. The wastewater treatment experimental conditions are shown in Table 3. The experimental raw water was taken from Quyang Pump Station, and the chemical oxygen demand (COD), ammonia nitrogen content (NH3-N) and total phosphorus content (TP) of the experimental inlet water quality are shown in Table 4. The experimental effluent water quality of the experimental device filled with different fillers is shown in Table 5.
[0140] Table 3: Sewage treatment experimental operation conditions
[0141]
[0142] Table 4: Experimental influent water quality
[0143] Water quality indicators COD(mg / L) <![CDATA[NH3-N(mg / L)]]> TP(mg / L) scope 150-258 30.1-39.4 9.15-11.7 Mean 189 34.9 10.37
[0144] Table 5: Experimental effluent quality
[0145]
[0146] In Table 5, the average COD removal rate is (daily influent COD-daily effluent COD) / average of daily influent COD, and the average NH3-N removal rate is (daily influent NH3-N-daily effluent NH3-N) / average of daily influent NH3-N.
[0147] The results in Table 5 show that compared with ordinary polyurethane sponge fillers, the polyurethane carbon nanotube composite filler of the present invention has a better sewage treatment effect, which is reflected in the higher COD removal rate and NH3-N removal rate. The polyurethane carbon nanotube composite filler with activated carbon has a very good COD removal effect, and the COD removal rate can reach more than 84%.
Claims
1. A polyurethane carbon nanotube composite filler for water treatment, characterized in that: The polyurethane carbon nanotube composite filler comprises a polyurethane sponge, carbon nanotubes adhered to the polyurethane sponge skeleton via polydopamine, and active particles with adsorption function; The specific surface area of the polyurethane carbon nanotube composite filler is 3.4-3.8m 2 / g; The carbon nanotubes are hydroxylated carbon nanotubes, carboxylated carbon nanotubes or carbonylated carbon nanotubes; The carbon nanotubes are multi-walled carbon nanotubes; The carbon nanotubes have a diameter of 20-30 nm and a length of 10-30 μm; The particle size of the polyurethane sponge is 10-50 mm; The active particles are selected from one or more of activated carbon, iron disulfide powder and zeolite; The particle size of the active particles is 100-200 meshes.
2. The method for preparing the polyurethane carbon nanotube composite filler according to claim 1, characterized in that: The method comprises: (1) Preparing a dopamine-modified solution: adding dopamine to a tris-HCl buffer solution and mixing well to obtain a dopamine-modified solution; (2) Prepare carbon nanotube modified solution and active particle modified solution: dispersing carbon nanotubes in a dopamine modified solution to obtain a carbon nanotube modified solution, dispersing active particles in a dopamine modified solution to obtain an active particle modified solution; (3) The polyurethane sponge is brought into contact with the carbon nanotube modification solution and the active particle modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
3. The method for preparing the polyurethane carbon nanotube composite filler according to claim 1, characterized in that: The method comprises: (1) Preparing a dopamine-modified solution: adding dopamine to a tris-HCl buffer solution and mixing well to obtain a dopamine-modified solution; (2) preparing a composite modified solution: dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution; (3) The polyurethane sponge is contacted with the composite modification solution so that the carbon nanotubes and active particles adhere to the polyurethane sponge skeleton.
4. The method for preparing the polyurethane carbon nanotube composite filler according to claim 1, characterized in that: The method comprises: (1) Preparing a dopamine-modified solution: adding dopamine to a tris-HCl buffer solution and mixing well to obtain a dopamine-modified solution; (2) Preparation of carbon nanotube modified solution and composite modified solution: dispersing carbon nanotubes in a dopamine modified solution to obtain a carbon nanotube modified solution, dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution; (3) contacting the polyurethane sponge with the carbon nanotube modification solution and the composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
5. The method for preparing the polyurethane carbon nanotube composite filler according to claim 1, characterized in that: The method comprises: (1) Preparing a dopamine-modified solution: adding dopamine to a tris-HCl buffer solution and mixing well to obtain a dopamine-modified solution; (2) Preparation of active particle modification solution and composite modification solution: dispersing the active particles in the dopamine modified solution to obtain an active particle modified solution, dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution; (3) The polyurethane sponge is brought into contact with the active particle modification solution and the composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
6. The method for preparing the polyurethane carbon nanotube composite filler according to claim 1, characterized in that: The method comprises: (1) Preparing a dopamine-modified solution: adding dopamine to a tris-HCl buffer solution and mixing well to obtain a dopamine-modified solution; (2) Preparing carbon nanotube modified solution, active particle modified solution and composite modified solution: dispersing carbon nanotubes in a dopamine modified solution to obtain a carbon nanotube modified solution, dispersing the active particles in the dopamine modified solution to obtain an active particle modified solution, dispersing carbon nanotubes and active particles in a dopamine modified solution to obtain a composite modified solution; (3) contacting the polyurethane sponge with the carbon nanotube modification solution, the active particle modification solution and the composite modification solution, so that the carbon nanotubes and the active particles adhere to the polyurethane sponge skeleton.
7. The method according to any one of claims 2 to 6, characterized in that The method has one or more of the following features: The pH of the tris-HCl buffer solution is 8-9; In the tris-HCl buffer solution, the concentration of tris(hydroxymethyl)aminomethane is 0.05-0.1 mol / L; In the dopamine-modified solution, the concentration of dopamine is 2-3 g / L.
8. The method according to claim 2, 4 or 6, characterized in that: In the carbon nanotube modified solution, the mass ratio of carbon nanotube to dopamine is 1:4-6.
9. The method according to claim 2, 5 or 6, characterized in that: In the active particle modified solution, the mass ratio of active particles to dopamine is 2:3 to 3:
2.
10. The method according to any one of claims 3 to 6, characterized in that: In the composite modified solution, the mass ratio of carbon nanotubes to dopamine is 1:4-6.
11. The method according to any one of claims 3 to 6, characterized in that: In the composite modified solution, the mass ratio of carbon nanotubes to active particles is 1:4-6.
12. The method according to claim 2, 4 or 6, characterized in that When preparing the carbon nanotube modified solution, the solution system is ultrasonically dispersed.
13. The method according to claim 12, characterized in that The ultrasonic dispersion time is 20-40 min.
14. The method according to claim 2, 5 or 6, characterized in that When preparing the active particle modified solution, the solution system is ultrasonically dispersed.
15. The method according to claim 14, characterized in that The ultrasonic dispersion time is 20-40 min.
16. The method according to any one of claims 3 to 6, characterized in that: When preparing the composite modified solution, the solution system is ultrasonically dispersed.
17. The method according to claim 16, characterized in that The ultrasonic dispersion time is 20-40 min.
18. The method according to claim 2, 4 or 6, characterized in that When the polyurethane sponge contacts the carbon nanotube modified solution, the volume ratio of the polyurethane sponge to the carbon nanotube modified solution is 5:95 to 20:
80.
19. The method according to claim 2, 5 or 6, characterized in that When the polyurethane sponge contacts the active particle modified solution, the volume ratio of the polyurethane sponge to the active particle modified solution is 5:95 to 20:
80.
20. The method according to any one of claims 3 to 6, characterized in that When the polyurethane sponge contacts the composite modified solution, the volume ratio of the polyurethane sponge to the composite modified solution is 5:95 to 20:
80.
21. The method of claim 2, 4 or 6, wherein: The polyurethane sponge is in contact with the carbon nanotube modified solution for 16-28 hours.
22. The method of claim 2, 5 or 6, wherein: The polyurethane sponge is in contact with the active particle modified solution for 16-28 hours.
23. The method according to any one of claims 3 to 6, characterized in that The polyurethane sponge is in contact with the composite modified solution for 16-28 hours.
24. The method of claim 2, 4 or 6, wherein: When the polyurethane sponge contacts the carbon nanotube modification solution, the reaction system of the polyurethane sponge and the carbon nanotube modification solution is stirred.
25. The method of claim 24, wherein: The stirring speed is 200-350 rpm.
26. The method of claim 2, 5 or 6, wherein: When the polyurethane sponge contacts the active particle modified solution, the reaction system of the polyurethane sponge and the active particle modified solution is stirred.
27. The method of claim 26, wherein: The stirring speed is 200-350 rpm.
28. The method according to any one of claims 3 to 6, characterized in that When the polyurethane sponge contacts the composite modified solution, the reaction system of the polyurethane sponge and the carbon nanotube modified solution is stirred.
29. The method of claim 28, wherein: The stirring speed is 200-350 rpm.
30. The method of claim 2, 4 or 6, wherein: The method further comprises washing and drying the polyurethane sponge after the polyurethane sponge is contacted with the carbon nanotube modification solution.
31. The method of claim 30, wherein: The drying temperature is 75-90℃ and the drying time is 12-16h.
32. The method of claim 2, 5 or 6, wherein: The method further includes washing and drying the polyurethane sponge after contacting the polyurethane sponge with the active particle modification solution.
33. The method of claim 32, wherein: The drying temperature is 75-90℃ and the drying time is 12-16h.
34. The method according to any one of claims 3 to 6, characterized in that The method further comprises washing and drying the polyurethane sponge after the polyurethane sponge is contacted with the composite modification solution.
35. The method of claim 34, wherein: The drying temperature is 75-90℃ and the drying time is 12-16h.
36. Use of the polyurethane carbon nanotube composite filler as claimed in claim 1 in a biofilm reactor.
37. The use according to claim 36, characterized in that The biofilm reactor is a moving bed biofilm reactor.
38. Use of the polyurethane carbon nanotube composite filler as claimed in claim 1 in water treatment.
39. A biofilm reactor or a water treatment device comprising a biofilm reactor, characterized in that: The biofilm reactor is filled with the polyurethane carbon nanotube composite filler according to claim 1.
40. The biofilm reactor or the water treatment device comprising the biofilm reactor according to claim 39, characterized in that: The biofilm reactor is a moving bed biofilm reactor.
Citation Information
Patent Citations
Preparation method and application of hydrophilic polyurethane porous carrier
CN102515341A
Modification method of polyurethane sponge packing and the modified hydrophilic polyurethane sponge packing
CN109399788A
Tourmaline / polyurethane compound filler and preparation method thereof
CN109607761A
Preparation method of modified polyurethane sponge filler for emergency of MBBR process
CN110563127A
Modified polyurethane sponge biological filler and preparation method thereof
CN110724304A